Uma investigação sobre a aprendizagem dos conceitos deevidência no laboratório escolar - Alessandro Damasio Trani Gomes (2009)
This thesis reviews the discussions about practical work and what students can learn by engaging in doing practical activities. A model for the kinds of knowledge students have to learn and mobilize in order to conduct laboratory work successfully is presented and used to assess students learning from lab work along a full school year. According to this model, procedural knowledge mobilized by students while conducting practical work is best conceived as composed of skills and techniques, and conceptual knowledge that affect their actions and thinking. The concepts of evidence refer either to conceptual knowledge needed to gather reliable and valid data, or to organize the information collected and interpret them properly to be assess the quality of evidence, to test hypothesis and explanations. The main aim of this work is to understand how students understanding about the process of experimentation develops, as well as their practical problem solving skills. We are also interested in identify how students epistemological knowledge and understanding of aspects related to the nature of science change along their first year of studying physics as a separate subject in secondary school. This is the first time that students have systematic laboratory activities. 250 students from the first year of a Brazilian Federal Middle School, corresponding to year 9 of compulsory education, took part in the study. A set of written tests were answered in the third and fourth weeks of the course, and repeated at the end of the school year. Besides that, several practical activities of two classes were observed and videorecorded. A small part of the students was interviewed either individually or in small groups. Based on the analyses conducted we argue that the engagement of students in practical activities contributed to promote their development of more sophisticated understandings of the concepts of evidence. In fact, in general, students showed better achievement in the posttests, although in a limited number of specific tests statistically significance was reached. Concerning the understanding of aspects of the nature of science, changes were limited and modest, a result not surprising taking into account the vast research literature about the theme, and for the fact that it was not a main purpose of the physics course. Based on these results, we discuss the implications for the teaching and the research on physics and science education.